The Effect Of International Accreditation On The Interest Of Students With Intellectual Capital Disclosure As A Moderation Variable At State University In Indonesia; Evidence From 4ICU 2022 - Pratiwi Fitri Wijayanti; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (Enrichment : Journal of Management, 2022)
This study aims to empirically examine the effect of international accredited study programs on student interest and the interaction of ICD as a moderating variable on the effect of accredited study programs on student interest. In addition, researchers show the practice of intellectual capital disclosure at the best state universities in Indonesia, the 4ICU version in 2022. The data is taken from the official website of universities in Indonesia. The results showed that from 46 samples of universities, there was no university that fully disclosed the Intellectual Capital indicator. In addition to human capital information, universities tend to report relational capital which indirectly describes the achievements and advantages of the university The results of the PLS test show that international accredited study programs have a significant effect on student interest and ICD does not moderate the relationship between international accredited study programs and student interests.